Serum extracellular vesicles profiling is associated with COVID‐19 progression and immune responses. Issue 4 (20th April 2022) - Yim, Kevin Ho Wai; Borgoni, Simone; Chahwan, Richard
Abstract: Coronavirus disease 2019 (COVID‐19) has transformed very quickly into a world pandemic with severe and unexpected consequences on human health. Concerted efforts to generate better diagnostic and prognostic tools have been ongoing. Research, thus far, has primarily focused on the virus itself or the direct immune response to it. Here, we propose extracellular vesicles (EVs) from serum liquid biopsies as a new and unique modality to unify diagnostic and prognostic tools for COVID‐19 analyses. EVs are a novel player in intercellular signalling particularly influencing immune responses. We herein show that innate and adaptive immune EVs profiling, together with SARS‐CoV‐2 Spike S1 + EVs provide a novel signature for SARS‐CoV‐2 infection. It also provides a unique ability to associate the co‐existence of viral and host cell signatures to monitor affected tissues and severity of the disease progression. And provide a phenotypic insight into COVID‐associated EVs.